Interaction of a non-aqueous solvent system on bamboo, cotton, polyester and their blends: the effect on abrasive wear resistance - SANCAK, ERHAN (ELSEVIER SCIENCE SA, 2015)
This article investigates the use of Trichloroacetic acid-Methylene chloride (TCAMC) solvent system with a view to study the abrasive wear resistance of bamboo, cotton, organic cotton, polyester (PES), cotton/bamboo and polyester/cotton blended woven fabrics. The fabrics were treated with different concentrations of 1%, 5% and 10% of TCAMC for 5, 30 and 60 mins at room temperature. Martindale Abrasion Tester was employed to test the abrasive wear resistance of fabrics. The weight loss of fabrics was checked after every 1000 abrasive cycles. The results suggest that the bamboo fabric, without TCAMC treatment, possesses an abrasive wear resistance that is comparable to that of organic cotton fabric. However, cotton/bamboo blend fabric was found to have enhanced abrasion wear resistance than that of 100% bamboo fabric. The results also indicate that the TCAMC treatment enhanced the abrasion wear resistance of 100% bamboo and 100% organic cotton fabrics. The treatment does not influence the wear resistance of 100% cotton and its blends. The abrasive wear resistance of untreated polyester (PES) fabric was tested and compared with cellulosics and it was found that PES possessed higher abrasive wear resistance. However, the abrasive wear resistance of TCAMC treated PES decreased considerably. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Trichloroacetic acid-Methylene chloride modification; Polymer modification; Bamboo; Organic cotton; Polyester; Abrasive wear resistance; FIBERS; FABRICS; YARNS